Performance Analysis of Inner Village Office Employees Providing Administrative Services to Community (Study at the Kareke Village Office, Dompu Regency) - Pardan, M. Wildan; Samsudin, Samsudin; Sumarni, Sumarni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the performance of Kareke Village Office employees in providing Administrative Services to the community. Qualitative Descriptive Research Method with a sample of 7 people consisting of the Village Head and several Staff and the community domiciled in Kareke Village, the sampling technique using purposive sampling. The results of the study indicate that in general the performance of employees at the Kareke Village Office is quite good, but there are still several obstacles, including the limited number of employees, lack of ongoing training, and inadequate facilities. Several aspects of service such as speed, accuracy, and friendliness in serving the community have been running, but in terms of service consistency and provision of information, improvements are still needed. Factors that support employee performance include the commitment of the Village apparatus and a fairly solid working relationship between employees. While the inhibiting factors include the lack of human resources and the limited Village budget